Paramedic Checklists do not Accurately Identify Post-ictal or Hypoglycaemic Patients Suitable for Discharge at the Scene. Issue 3 (30th March 2016) - Tohira, Hideo; Fatovich, Daniel; Williams, Teresa A.; Bremner, Alexandra; Arendts, Glenn; Rogers, Ian R.; Celenza, Antonio; Mountain, David; Cameron, Peter; Sprivulis, Peter; Ahern, Tony; Finn, Judith
Abstract: Objectives: The objective of this study was to assess the accuracy and safety of two pre-defined checklists to identify prehospital post-ictal or hypoglycemic patients who could be discharged at the scene. Methods: A retrospective cohort study of lower acuity, adult patients attended by paramedics in 2013, and who were either post-ictal or hypoglycemic, was conducted. Two self-care pathway assessment checklists (one each for post-ictal and hypoglycemia) designed as clinical decision tools for paramedics to identify patients suitable for discharge at the scene were used. The intention of the checklists was to provide paramedics with justification to not transport a patient if all checklist criteria were met. Actual patient destination (emergency department [ED] or discharge at the scene) and subsequent events (eg, ambulance requests) were compared between patients who did and did not fulfill the checklists. The performance of the checklists against the destination determined by paramedics was also assessed. Results: Totals of 629 post-ictal and 609 hypoglycemic patients were identified. Of these, 91 (14.5%) and 37 (6.1%) patients fulfilled the respective checklist. Among those who fulfilled the checklist, 25 (27.5%) post-ictal and 18 (48.6%) hypoglycemic patients were discharged at the scene, and 21 (23.1%) and seven (18.9%) were admitted to hospital after ED assessment. Amongst post-ictal patients, those fulfilling the checklist had more subsequent ambulance requests (P=.01) and ED attendances with seizure-related conditions (P=.04) within three days than those who did not. Amongst hypoglycemic patients, there were no significant differences in subsequent events between those who did and did not meet the criteria. Paramedics discharged five times more hypoglycemic patients at the scene than the checklist predicted with no significant differences in the rate of subsequent events. Four deaths (0.66%) occurred within seven days in the hypoglycemic cohort, and none of them were attributed directly to hypoglycemia. Conclusions: The checklists did not accurately identify patients suitable for discharge at the scene within the Emergency Medical Service. Patients who fulfilled the post-ictal checklist made more subsequent health care service requests within three days than those who did not. Both checklists showed similar occurrence of subsequent events to paramedics' decision, but the hypoglycemia checklist identified fewer patients who could be discharged at the scene than paramedics actually discharged. Reliance on these checklists may increase transportations to ED and delay initiation of appropriate treatment at a hospital. H Tohira, D Fatovich, TA Williams, A Bremner, G Arendts, IR Rogers, A Celenza, D Mountain, P Cameron, P Sprivulis, T Ahern, J Finn .Paramedic checklists do not accurately identify post-ictal or hypoglycaemic patients suitable for discharge at the scene .Prehosp Disaster Med .2016 ;31 (3 ):282 –293 .